As inter-relações entre universidade e escola básica: o estágio e a prática de futuros professores das séries iniciais na construção de conhecimentos pedagógicos da matemática - Mioto, Rodrigo (2008)
This document aims to investigate the knowledge construction for teaching Mathematics in the initial series. It intends to bring contribution for the initial formation improvement of the initial series teachers, being the trainee a reference point. The perspective is to identify Mathematic knowledge that this future teacher purchases during your formation at the University and at the school that the stage was developed. Contacting a University that offers the Pedagogy course, was selected a student that realized the supervised stage, indicated by the professor of this subject. The teacher of the discipline 'Mathematics Content and Methodology' from the Pedagogy Course and the regent teacher with whom was realized the stage in the Basic Education school were part of the research. It was investigated the proposals of the educational project and the Supervised Stage Manual related to the formation of a critic, investigative and reflexive professional on Mathematics contents; the opportunities for investigation, reflection and critic moments about Mathematics teaching and learning process on stage activities and practices and the regent teacher's contribution to the construction of a educational mathematics knowledge for the future teacher of initial series. Based on the research of Tardif (2002) about teacher knowledge and professional formation, Pimenta (2008) about stage and teaching, Curi (2004) about initial series teachers formation, Shulman (2004) about knowledge base categories for the teacher and Alarcão (2008) about the reflection in teaching. The data were obtained through documentary analysis and half-structured with two teachers of a Pedagogy course, a student that realized the stage, and the regent teacher of the school. The distance between the university and the school, pointed by several researches, prevails in this investigation, and it's up to the trainee the responsibility to realize his stage, according to the documents of institution and guidance of the regent teacher. This responsibility should be discussed, reflected and investigated by the formation agents